A methodological roadmap to quantify animal‐vectored spatial ecosystem subsidies. Issue 7 (3rd June 2021) - Ellis‐Soto, Diego; Ferraro, Kristy M.; Rizzuto, Matteo; Briggs, Emily; Monk, Julia D.; Schmitz, Oswald J.
Abstract: Energy, nutrients and organisms move over landscapes, connecting ecosystems across space and time. Meta‐ecosystem theory investigates the emerging properties of local ecosystems coupled spatially by these movements of organisms and matter, by explicitly tracking exchanges of multiple substances across ecosystem borders. To date, meta‐ecosystem research has focused mostly on abiotic flows—neglecting biotic nutrient flows. However, recent work has indicated animals act as spatial nutrient vectors when they transport nutrients across landscapes in the form of excreta, egesta and their own bodies. Partly due to its high level of abstraction, there are few empirical tests of meta‐ecosystem theory. Furthermore, while animals may be viewed as important mediators of ecosystem functions, better integration of tools is needed to develop predictive insights of their relative roles and impacts on diverse ecosystems. We present a methodological roadmap that explains how to do such integration by discussing how to combine insights from movement, foraging and ecosystem ecology to develop a coherent understanding of animal‐vectored nutrient transport on meta‐ecosystems processes. We discuss how the slate of newly developed technologies and methods—tracking devices, mechanistic movement models, diet reconstruction techniques and remote sensing—that when integrated have the potential to advance the quantification of animal‐vectored nutrient flows and increase the predictive power of meta‐ecosystem theory. We demonstrate that by integrating novel and established tools of animal ecology, ecosystem ecology and remote sensing, we can begin to identify and quantify animal‐mediated nutrient translocation by large animals. We also provide conceptual examples that show how our proposed integration of methodologies can help investigate ecosystem impacts of large animal movement. We conclude by describing practical advancements to understanding cross‐ecosystem contributions of animals on the move. Understanding the mechanisms by which animals shape ecosystem dynamics is important for ongoing conservation, rewilding and restoration initiatives around the world, and for developing more accurate models of ecosystem nutrient budgets. Our roadmap will enable ecologists to better qualify and quantify animal‐mediated nutrient translocation for animals on the move. Abstract : Incorporation of animal subsidies into biogeochemical budgets has been hampered by large degree of abstraction and little overview on disparate fields necessary to 'animate' ecosystem budgets. The authors provide a methodological roadmap to aid the design and implementation of these studies, demonstrating the power of integrating tools from all three fields.